Karakteristik Beberapa Jamur Liar dari Hutan Pendidikan Anggori, Papua Barat: Characteristics of Several Wild Mushrooms from the Anggori Research Forest, West Papua - Chesa Devi Aksa Yahya; Raditya Febri Puspitasari; Muhammad Almaz Misykah Mufti; Descarlo Worabai; Nunang L. May; Evelin A. Tanur; Ivan Permana Putra (Departemen Biologi, Institut Pertanian Bogor, 2026)
The Anggori Educational Forest in Manokwari, West Papua, is a lowland tropical rainforest with high biodiversity, but information on fungi in this region is still very limited. This study aims to identify, characterize the morphology, and inventory wild mushroom in the Anggori Educational Forest. Sampling was conducted in December 2025 using the opportunistic sampling method, followed by macroscopic and microscopic observations in January-February 2026. The results of the study successfully identified four fungal taxa consisting of the Basidiomycota phylum, namely Marasmius sp.1, Marasmius sp.2, and Gymnopilus sp., and the Ascomycota phylum, namely Xylaria sp. The Marasmius genus was found abundantly on litter and twig substrates with the ability to rehydration. Gymnopilus sp. was found growing in colonies on littered soil, while Xylaria sp. was found on decaying wood with the characteristic hard stroma that resembles a finger (dead man's finger). The shaded microclimate conditions of the Anggori Forest, high humidity (>80%), and the availability of abundant organic material are the main supporting factors for fungal diversity in this area.